Drivers of youth engagement in agriculture: Insights from Guatemala, Niger, Nigeria, Rwanda, and Uganda - Babu, Suresh Chandra; Franzel, Steven; Davis, Kristin E.; Srivastava, Nandita (International Food Policy Research Institute, 2021)
Engaging burgeoning youth populations in developing country agriculture is seen as an important strategy toward effective, efficient, and sustainable food system transformation. Yet the policy, institutional, technological, and capability barriers and ways to overcome them for successful participation of youth in agriculture are not fully understood. We use a conceptual framework that identifies key pathways to prosperity for youth and classifies contextual and driving factors that contribute to the success of youth engagement in agriculture. The framework comprises four broad categories of strategic interventions: and socioeconomic environment; institutional; technological/business infrastructure; and individual skills and capacities. In the context of this framework, we then present insights from cases of youth participation in agriculture in five countries: Guatemala, Niger, Nigeria, Rwanda, and Uganda. The countries and cases were purposively selected as part of ongoing research on youth engagement in agriculture. Policies and strategies play an important role in creating an enabling environment for youth engagement in agriculture, including by fostering transparency and accountability in the system and promoting youth engagement in the private sector through agricultural extension and other services. Institutions and intermediaries provide financial support, training, and access to market for youth entrepreneurs. Support in these areas should be strengthened. Systems approaches, such as multi-stakeholder platforms, provide holistic support to young agripreneurs (entrepreneurs in agriculture), but require effective coordination. Similarly, information and communication technologies can play a facilitating role by providing platforms to network and receive updated market information but need to be significantly scaled up. Individual capacities can drive youth engagement in agriculture and agripreneurship but must continue to be built up through expanded education and training on technical and functional skills. As policymakers and program managers search for interventions that can promote youth involvement in agriculture in their own countries, the insights from the five countries examined that are presented in this paper may be useful for identifying context-specific challenges and pathways to successful youth engagement in agriculture in their own countries. The framework presented here can be applied to study youth engagement issues in any country or in sub-national, decentralized contexts to generate evidence to guide the design of youth-in-agriculture development programs. There is a need to support, strengthen, and implement the driving factors identified in this paper for expanding youth engagement in agriculture.